Transcriptomic analysis reveals long non-coding RNA involved in the key metabolic pathway in response to Botrytis cinerea in kiwifruit - Yijia Ma; Tianjing Zeng; Zhexin Li; Dengwei Jue; Yuan Sui; Xu Wang; Hongpan Zhong; Jiaqi Yang (BMC Plant Biology)
Abstract Background Understanding the molecular mechanisms that confer kiwifruit resistance to Botrytis cinerea is essential for developing resistant cultivars. Long non-coding RNAs (lncRNAs), known to participate in various physiological processes including plant defense against diseases, have an undefined role in kiwifruit’s resistance. Results Our study aimed to identify lncRNAs induced by B. cinerea infection in ‘Hongyang’ kiwifruit at 0 to 3 days post-inoculation (dpi) through high-throughput sequencing. The differential expression analysis identified 126 differentially expressed lncRNAs (DELs). Subsequent GO and KEGG analyses indicated that these lncRNAs’ target genes were predominantly associated with plant-pathogen interactions, carbohydrate metabolism including starch and sucrose, mitogen-activated protein kinase (MAPK) signaling pathways, and plant hormone signal transduction. Co-expression analysis revealed that lncRNAs modulate the expression of genes involved in phytohormone signaling pathways, such as those for auxin, ethylene (ETH), abscisic acid (ABA), jasmonic acid (JA), and salicylic acid (SA), as well as the MAPK signaling pathway. This regulation affects the biosynthesis of defense-related secondary metabolites like ADP-glucose, sucrose, 1,3-β-glucan, and cellulose, thereby enhancing the fruit’s disease resistance. Conclusion Our findings offer valuable insights into the mechanisms by which lncRNAs respond to biotic stress in kiwifruit, potentially aiding in the development of strategies for breeding kiwifruit with improved resistance to B. cinerea.